Changes following Premarital Education for Couples with Differing Degrees of Future Marital Risk. - Barton, Allen W.; Futris, Ted G.; Bradley, Renay C. (Journal of Marital & Family Therapy, 2014)
The present study explored changes in individuals' relationship cognitions and behaviors following premarital education for couples with different risk profiles. The sample consisted of 63 couples who completed the PREPARE program and were classified for future marital risk based on dyadic information. A significant interaction effect was found between risk and time, with individuals in relationships classified as high risk exhibiting greater change at 4 weeks postprogram compared to low-risk individuals. Perceived helpfulness of topics also varied by couple type. Findings provide support for adapting premarital education programs for high-risk couples and offer clinicians and educators specific insights for areas of emphasis when working with different types of couples.